Transportation Service and Student’s Satisfaction: A Study on Dhaka University (Indian Journal of Social Science and Literature (IJSSL), 2024)
This paper attempts to explore the level of satisfaction of the Students of the Dhaka University, Bangladesh regarding the transportation Services provided to them by the university authority. The Study also provides detailed accounts of the transport patterns and transportation services, problems and issues faced by students who commute regularly in university buses. A cross-sectional survey has been conducted to investigates relevant issues of Transportation Services, its barriers and User preferences and explores the main transport challenges faced by the students. Results have been obtained following a survey designed in mix approach of research. A total of 340 respondents were collected following a quota sampling using well designed questionnaire where an equal male-female ratio of the respondents was strictly maintained. Study found that users scored the ‘comfort’ as the lowest (40%) feature of the university transportation services. Students shared their sufferings as well as positive impacts of University Transportation services in this Study. The saddest part of the findings of this study is that there is no specific provision for the students with special needs in the university transports. Having no ‘Transportation Policy’ might cause this sort of lacking among all others. So, it can be expected that the university authority will take necessary actions to have a sound transportation policy in near future. At the end, some recommendations have been put here to get these reflected in the policy to make it a sustainable and inclusive one.